Isolation and Identification of Endophytic Yeast from Sugarcane Juice (Saccharum officinarum L.) as a Bread Leavening Agent - Nur Kusmiyati; Ulfah Utami; Anindita Mahesa Fitri; Anggeria Oktavisa Denta; Toshifumi Sakaguchi (Journal of Mathematical and Fundamental Sciences, 2025)
Baker’s yeast naturally occurs in plant materials with high glucose content, including sugarcane (Saccharum officinarum L.). This study aimed to isolate and identify yeast from sugarcane juice and evaluate its safety and potential application as baker’s yeast. The methodological workflow included isolation, purification, macroscopic and microscopic characterization, and molecular identification. Safety assessments consisted of hemolysis testing and the evaluation of phospholipase and protease enzyme activities. The technological potential of the isolates was examined through carbohydrate fermentation, tolerance to 50% glucose, flocculation capacity, and hydrogen sulfide production. Two isolates, designated SO1 and SO2, were successfully obtained. Molecular characterization revealed that SO1 shared 99.20% similarity with Hanseniaspora opuntiae, while SO2 showed 99.98% similarity with Candida akabanensis. Both isolates exhibited non-pathogenic characteristics, indicated by a hemolysis index (Hi) of 1 and phospholipase activity represented by a precipitation zone (Pz) of 1. Protease activity assay showed Pz values of 1 for H. opuntiae and 0.58 for C. akabanensis. Potency testing demonstrated that both species performed well in bread dough development, confirming promising leavening capabilities. Overall, H. opuntiae and C. akabanensis isolated from sugarcane juice are food-grade yeasts and are safe for use in bread production.